Prognostic effects of delirium motor subtypes in hospitalized older adults: A prospective cohort study - Avelino-Silva, Thiago Junqueira (PLoS One, 2018)
OBJECTIVES: To investigate the association between delirium motor subtypes and hospital mortality and 12-month mortality in hospitalized older adults. DESIGN: Prospective cohort study conducted from 2009 to 2015. SETTING: Geriatric ward of a university hospital in Sao Paulo, Brazil. PARTICIPANTS: We included 1,409 consecutive admissions of acutely ill patients aged 60 years and over. We excluded admissions for end-of-life care, with missing data on the main variables, length of stay shorter than 48 hours, or when consent to participate was not given. MAIN OUTCOMES AND MEASURES: Delirium was detected using the Confusion Assessment Method and categorized in hypoactive, hyperactive, or mixed delirium. Primary outcomes were time to death in the hospital, and time to death in 12 months (for the discharged sample). Comprehensive geriatric assessment was performed at admission and included socio-demographic, clinical, functional, cognitive, and laboratory variables. Further clinical data were documented upon death or discharge. Multivariate analyses used Cox proportional hazards models adjusted for possible confounders. RESULTS: We included 1,409 admissions, with a mean age of 80 years. The proportion of in-hospital deaths was 19%, with a cumulative mortality of 38% in 12 months. Delirium occurred in 47% of the admissions. Hypoactive delirium was the predominant motor subtype (53%), followed by mixed delirium (30%) and hyperactive delirium (17%). Hospital mortality rates were respectively 33%, 34% and 15%. We verified that hypoactive and mixed delirium were independently associated with hospital mortality, with respective hazard ratios of 2.43 (95%CI = 1.64–3.59) and 2.31 (95%CI = 1.53–3.50). Delirium motor subtypes were not independently predictive of 12-month mortality. CONCLUSIONS: One in three acutely ill hospitalized older adults who suffered hypoactive or mixed delirium died in the hospital. Clinicians should be aware that hypoactive symptoms of delirium, whether shown exclusively or in alternation with hyperactive symptoms, are indicative of a worse prognosis in this population.